Contribution of education level and dairy fat sources to serum cholesterol in Russian and Finnish Karelia: results from four cross-sectional risk factor surveys in 1992-2007 - Paalanen Laura; Prättälä Ritva; Laatikainen Tiina (BMC, 2012)
Abstract Background Food habits vary by socio-economic group and geographic area. Data on socio-economic differences in food habits and in serum total cholesterol concentration from Russia are scarce. Our aim was to examine changes and educational differences in serum total cholesterol and in the consumption of major sources of saturated fat in two geographically neighbouring areas, Russian and Finnish Karelia, and to examine whether the foods associated with serum total cholesterol are different in the two areas. Methods Data from cross-sectional risk factor surveys from years 1992, 1997, 2002 and 2007 in the district of Pitkäranta, the Republic of Karelia, Russia (n = 2672), and North Karelia, Finland (n = 5437), were used. The analyses included two phases. 1) To examine the differences in cholesterol by education, the means and 95% confidence intervals for education groups were calculated for each study year. 2) Multivariate linear regression analysis was employed to examine the role of butter in cooking, butter on bread, fat-containing milk and cheese in explaining serum total cholesterol. In these analyses, the data for all four study years were combined. Results In Pitkäranta, serum total cholesterol fluctuated during the study period (1992-2007), whereas in North Karelia cholesterol levels declined consistently. No apparent differences in cholesterol levels by education were observed in Pitkäranta. In North Karelia, cholesterol was lower among subjects in the highest education tertile compared to the lowest education tertile in 1992 and 2002. In Pitkäranta, consumption of fat-containing milk was most strongly associated with cholesterol (β=0.19, 95% CI 0.10, 0.28) adjusted for sex, age, education and study year. In North Karelia, using butter in cooking (β=0.09, 95% CI 0.04, 0.15) and using butter on bread (β=0.09, 95% CI 0.02, 0.15) had a significant positive association with cholesterol. Conclusions In the two geographically neighbouring areas, the key foods influencing serum cholesterol levels varied considerably. Assessment and regular monitoring of food habits are essential to plan nutrition education messages that are individually tailored for the target area and time.